Pengaruh Motivasi Dan Persepsi Pengunjung Terhadap Keputusan Berkunjung Ke Pedestrian Sudirman Palembang - Natanael Mangasi Simanjuntak; Desloehal Djumrianti; Lisnini Lisnini (Politeknik Negeri Sriwijaya, 2020)
One of the new tourism objects developing in Palembang City is the Sudirman Palembang Pedestrian night tour. The purpose of this study was to determine the influence of motivation and visitor perceptions on the decision to visit Pedestrian Sudirman Palembang. The sample in this study used the Probability Sampling technique with a simple random sampling approach. The number of samples in this study was 100 respondents. This study found that the variables of motivation and visitor perceptions influence the decision to visit both simultaneously and partially. There are several things that motivate and perceptions to visit the Pedestrian Sudirman Palembang, namely because Pedestrian Sudirman is a comfortable place to spend leisure time, there are many choices of food and drinks, as well as music, art and dance attractions. The government of Palembang City is expected to be able to make improvements to parking facilities because the average respondent feels that the parking facilities at this tourist attraction are inadequate so this can be a negative perception for visitors which can lead to a decrease in visits.